Recent Research Progress on Ground-to-Air Vision-Based Anti-UAV Detection and Tracking Methodologies: A Review - Arowa Yasmeen; Ovidiu Daescu (Drones)
Unmanned Aerial Vehicles (UAVs) are increasingly gaining popularity, and their consistent prevalence in various applications such as surveillance, search and rescue, and environmental monitoring requires the development of specialized policies for UAV traffic management. Integrating this novel aerial traffic into existing airspace frameworks presents unique challenges, particularly regarding safety and security. Consequently, there is an urgent need for robust contingency management systems, such as Anti-UAV technologies, to ensure safe air traffic. This survey paper critically examines the recent advancements in ground-to-air vision-based Anti-UAV detection and tracking methodologies, addressing the many challenges inherent in UAV detection and tracking. Our study examines recent UAV detection and tracking algorithms, outlining their operational principles, advantages, and disadvantages. Publicly available datasets specifically designed for Anti-UAV research are also thoroughly reviewed, providing insights into their characteristics and suitability. Furthermore, this survey explores the various Anti-UAV systems being developed and deployed globally, evaluating their effectiveness in facilitating the integration of small UAVs into low-altitude airspace. The study aims to provide researchers with a well-rounded understanding of the field by synthesizing current research trends, identifying key technological gaps, and highlighting promising directions for future research and development in Anti-UAV technologies.